Problematizing "authenticity" : a critical appraisal of the Jamaat-i-Islami gender discourse - Cheema, Shahbaz Ahmad (2011)
Islamic practices have led to exhaustive debate in academia ranging from the traditional battlefield of gender related issues to the relatively new decisiveness surrounding the war on terror. In most of the debates regarding Islam, when one legitimises or delegitimises his/her stance, the divine is invoked as the main point of reference. The divine thus turns into the source of vice and virtue simultaneously through these competing opinions. In this game of "authenticity", we often ignore the aspect that, in our religious zealousness, the divine itself is victimised. This is because, while referring to the divine as the main architect of our opinions, we sideline those non-divine factors in the process of constructing "authenticities" which help shape our reading of the divine. The divine is simply a part of our constructed "authenticity" but not its exclusive constituent. We need to realise that the divine is not read in a vacuum and by those who do not have materiality; its readings are always carried out by those who are a product of their own circumstances and their understandings are routed through their particular contexts. The present study is an effort to analyse those non-divine factors which help shape our reading of the divine, and are not any less important in the process of constructing "authenticity" than the divine with reference to the gender discourse of Jamaat-i-Islami Pakistan. This study proposes that there is always a need to maintain a gap between our understanding of the divine and "the divine"; because of the fact that the former is constructed, while the latter believed by Muslims as eternal, hence immutable. In addition to carrying out problematization of "authenticity" of the JI discourse, the study underscores the fact that problematization ought to be an integral part of our exercise of ascertainment of "authenticity" so that we may maintain the gap referred to above.